The reformation of the English parish church - Whiting, Robert (Cambridge Univ. Press, 2010)
"In the sixteenth century, the people of England witnessed the physical transformation of their most valued buildings: their parish churches. This is the first ever full-scale investigation of the dramatic changes experienced by the English parish church during the English reformation. By drawing on a wealth of documentary evidence, including court records, wills and church wardens' accounts, and by examining the material remains themselves - such as screens, fonts, paintings, monuments, windows and other artefacts - found in churches today, Robert Whiting reveals how, why and by whom these ancient buildings were transformed. He explores the reasons why catholics revered the artefacts found in churches as well as why these objects became the subject of protestant suspicion and hatred in subsequent years. This richly illustrated account sheds new light on the acts of destruction as well as the acts of creation that accompanied religious change over the course of the 'long' reformation"--Provided by publisher